La muerte de Eurídice: sobre el hidro, el quersidro y el quelidro - Ruiz de Elvira, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2004)
Analysis of the ancient literary sources about Eurydice’s death and discussion about the type of snake mentionend by Vergil in georg. 4, 458.